Information technologies in the education of contemporary China: reality and opportunities - Sun, Wei (Інститут вищої освіти Національної Академії педагогічних наук України, 2023)
With the rapid development of modern information technologies, their integration into all areas of education is accelerating, which contributes to the penetration of innovations into the education space. The author emphasizes that the design of many educational technologies was focused on the goals of education and included a sufficient number of educational concepts and elements. However, if teachers blindly adhere to the traditional concept of “technology is only a tool”, then this creates a sense of superiority of their own status and a narrow understanding of the value of technology. The author relies in his research on the latest achievements in the field of not only high technologies that are used in education, but also on psychological and social research on the impact of the latter both on education and on a person. The author proposes to perceive technologies in the context of a new culture, and shows possible ways of their more adequate use. Working with artificial technological objects is not only the acceptance of an artificial object, but also the adoption of a technical culture, which indicates a new cultural relationship between people and technology, and vice versa. On the basis of analyzing the phenomenon and essence of contemporary information technology, the author of this article tries to find out the problems existing in the application of contemporary information technology in education through a questionnaire survey, and reflects on the influence of technology on teachers and students in the education system. The answers of the survey participants made it possible to present a picture of the use of information technologies in education as a holistic and complex process. The analysis of the results obtained, as well as everyday practical training in the skills of using high technologies, enabled the author to establish that the influence of information technologies on education is complex, this is a new stage in the development of education as a whole, which allows us to characterize the process of their use as a holistic system. The influence of technology has completely changed all structures and all participants in education. The results of the survey also made it possible to identify a number of problems that indicate shortcomings in the modern space of education, the didactic nature of learning in the sense of conveying and receiving information in new conditions (we are talking not only about digitalization as a process, but also about changes aimed at transforming teaching methodology).

Зі стрімким розвитком сучасних інформаційних технологій прискорюється їх інтеграція в усі сфери освіти, що сприяє проникненню інновацій в освітній простір. Авторка підкреслює, що розробка багатьох освітніх технологій була орієнтована на цілі навчання і включала достатню кількість освітніх понять і елементів. Проте, якщо вчителі сліпо дотримуються традиційної концепції «технологія – це лише інструмент», то це створює відчуття вищості власного статусу та вузьке розуміння цінності технологій. У своїх дослідженнях авторка спирається на новітні досягнення в галузі не тільки високих технологій, які використовуються в освіті, а й на психологічні та соціальні дослідження щодо впливу останніх як на освіту, так і на людину. Авторка пропонує сприймати технології в контексті нової культури, показує можливі шляхи їх більш адекватного використання. Робота зі штучними технологічними об’єктами – це не тільки прийняття штучного об’єкта, а й прийняття технічної культури, яка вказує на нові культурні відносини між людьми та технологією, і навпаки. На основі аналізу явища та сутності сучасних інформаційних технологій авторка статті шляхом анкетного опитування намагається з’ясувати проблеми, які існують у застосуванні сучасних інформаційних технологій в освіті, розмірковує про вплив технологій на педагогів і педагогів. учнів у системі освіти. Відповіді учасників опитування дали змогу скласти картину використання інформаційних технологій в освіті як цілісного та комплексного процесу. Аналіз отриманих результатів, а також повсякденне практичне навчання навикам використання високих технологій дозволили авторці встановити, що вплив інформаційних технологій на освіту є комплексним, це новий етап у розвитку освіти в цілому, що дозволяє охарактеризувати процес їх використання як цілісну систему. Вплив технологій повністю змінив усі структури та всіх учасників освіти. Результати опитування також дозволили виявити низку проблем, які свідчать про недоліки сучасного освітнього простору, про дидактичність навчання в сенсі передачі та сприйняття інформації в нових умовах (мова йде не тільки про цифровізацію як процес, а й про зміни, спрямовані на трансформацію методології навчання).
Інформаційні технології в освіті сучасного Китаю: реаль- ність і можливості
Keywords: education; high technology; "smart classroom"; "flipped classroom"; basic needs for information technology; integration of information technology in education; adaptation to the information environment; освіта; високі технології; "розумний клас"; "перевернутий клас"; базові потреби в інформаційних технологіях; інтеграція інформаційних технологій в освіту; адаптація до інформаційного середовища